Access to parks and physical activity: an eight country comparison - Schipperijn, Jasper; Cerin, Ester; Adams, Marc A; Reis, Rodrigo; Smith, Graham; Cain, Kelli; Christiansen, Lars B; van Dyck, Delfien; Gidlow, Christopher; Frank, Lawrence D; Mitáš, Josef; Pratt, Michael; et al. (Urban forestry & urban greening, 2017)
Several systematic reviews have reported mixed associations between access to parks and physical activity, and suggest that this is due to inconsistencies in the study methods or differences across countries. An international study using consistent methods is needed to investigate the association between access to parks and physical activity. The International Physical Activity and Environment Network (IPEN) Adult Study is a multi-country cross-sectional study using a common design and consistent methods. Accelerometer, survey and Geographic Information Systems (GIS) data for 6,181 participants from 12 cities in 8 countries (Belgium, Brazil, Czech Republic, Denmark, Mexico, New Zealand, UK, USA) were used to estimate the strength and shape of associations of 11 measures of park access (1 perceived and 10 GIS-based measures) with accelerometer-based moderate-to-vigorous physical activity (MVPA) and four types of self-reported leisure-time physical activity. Associations were estimated using generalized additive mixed models. More parks within 1 km from participants' homes were associated with greater leisure-time physical activity and accelerometer-measured MVPA. Respondents who lived in the neighborhoods with the most parks did on average 24 minutes more MVPA per week than those living in the neighborhoods with the lowest number of parks. Perceived proximity to a park was positively associated with multiple leisure-time physical activity outcomes. Associations were homogeneous across all cities studied. Living in neighborhoods with many parks could contribute with up to 1/6 of the recommended weekly Having multiple parks nearby was the strongest positive correlate of PA. To increase comparability and validity of park access measures, we recommend that researchers, planners and policy makers use the number of parks within 1 km travel distance of homes as an objective indicator for park access in relation to physical activity.
Keywords: exercise; multi-country; IPEN; leisure-time; GIS; accelerometry; recreation